Affin Credit (Malaysia) Sdn. Bhd. V. Yap Yuen Fei: The Denouement Of A Hire-Purchase Mystery? - Balan, P. (Journal of Malaysian and Comparative Law, 2019)
Malaysia's first and parent statute on hire-purchase, the Hire Purchase Act 1967, came into force on 11th April 1968. Although the bulk of the new Act was borrowed from the Hire-Purchase Act 1960-1965 of the Australian state of New South Wales, a number of significant innovations were incorporated into the Malaysian statute by the draftsman. The Malayasian statute was revised and re-enacted in 1978 as the Hire-Purchase Act 1967 (Revised 1978), incorporating amendments made in 1968, 1969 and 1976.